2020
DOI: 10.1002/ptr.6621
|View full text |Cite
|
Sign up to set email alerts
|

Natural products for the prevention and treatment of cholestasis: A review

Abstract: Cholestasis is a common manifestation of decreased bile flow in various liver diseases. It results in fibrosis and even cirrhosis without proper treatment. It is believed that a wide range of factors, including transporter dysfunction, oxidative stress, inflammatory damage, and immune disruption, can cause cholestasis. In recent years, natural products have drawn much attention for specific multiple-target activities in diseases. Many attempts have been made to investigate the anticholestatic effects of natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 136 publications
0
27
0
Order By: Relevance
“…However, traditional Chinese medicine has been widely used in alleviating liver fibrosis and cirrhosis. Yinchenhao decoction has a significant effect in the treatment of cholestatic hepatitis related to its repair of liver damage, reversing steatosis and fibrosis and exerting; anti‐inflammatory and antiviral effects and so forth (Lee, 2009; Ma et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, traditional Chinese medicine has been widely used in alleviating liver fibrosis and cirrhosis. Yinchenhao decoction has a significant effect in the treatment of cholestatic hepatitis related to its repair of liver damage, reversing steatosis and fibrosis and exerting; anti‐inflammatory and antiviral effects and so forth (Lee, 2009; Ma et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Some natural products have exhibited therapeutic effects on liver diseases for thousands of years. In particular, several kinds of representative natural products, such as flavonoids, quinones, lignans, phenols, and acids, demonstrate potent function in liver protection, cholestasis prevention, NASH inhibition, and hepatocellular carcinoma (HCC) suppression [ 9 , 10 ]. In addition, natural products that have promising efficacy in preventing fibrosis have been under rapid development [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant-derived flavonoids and phenolic acids have strong antioxidant properties and are known to prevent inflammatory diseases, cancer, cardiovascular diseases, and various degenerative diseases associated with oxidative stress [ 13 , 43 ]. Previous studies have found that rutin and chlorogenic acid are the main components of D. morbifera leaves, which is consistent with the findings of this study [ 19 ].…”
Section: Discussionmentioning
confidence: 99%